EFFECT OF FORMATIVE TESTING ON STUDENTS ACHIEVEMENT IN JUNIOR SECONDARY SCHOOL MATHEMATICS - Ajogbeje Oke James (European Scientific Journal, ESJ, 2012)
The concern about improving the outcome of mathematics instruction requires that concerted efforts be made to find out an instructional strategy that can be used and operated upon in order to improve the quality of secondary school graduates in mathematics. Hence, this study investigated the effect of formative testing on students’ achievement in junior secondary school mathematics. The research design is quasi – experimental design. The sample consisted of 312 JSS II students assigned to three experimental groups and one control group. Four instruments including three formative tests and Mathematics Achievement Test (MAT) were constructed, validated, and used for the collection of all revelant data. The data collected were analyzed using t – test and Analysis of Covariance (ANCOVA). The results of the study revealed that there was a significant difference in the level of achievement of members of the four treatment groups in their posttest scores after correcting for initial group differences. The formative test with feedback and remediation group performed better than the other three groups. The results of the study also revealed that male students did not perform better than female students in the posttest score.